Updated Theoretical View on the Principle of the Most Favored Nation in the Modern International Law Order - V. M. Shumilov (Московский журнал международного права, 2025)
INTRODUCTION. The principle of most favored nation (MFN) has long been used as an international legal instrument for regulating international trade between States in relation to customs duty rates. The main feature of the principle lies in the role that a third State plays in a bilateral legal relationship: participants (subjects) of a legal relationship are required to automatically provide the partner State (the authorized party) with any benefit granted to any third state, for example, a low rate of customs duty on imported goods or commodities. And, on the contrary, has the right to demand and receive such a privilege from the obligated party. The provision or receipt of a reduced rate for goods from the partner state is formalized and carried out by an act or acts of internal law (customs tariff, customs code, etc.), and this introduces a change in the internal customs regime of the interacting states. The principle of the most favored nation between two States is enforced and applies if the partner States receive benefits for goods in the partner State under the same most-favored-nation regime in comparison with the benefits granted to a third State for similar goods. The need to compare, contrast and equalize internal legal regimes in a coordinated sphere of relations at the most favorable level is an essential feature of the MFN principle, the main specific method of regulation. Over the past centuries, the MFN principle has come a long way in its formation and development, and today a new look at it is needed.MATERIALS AND METHODS. The study of this topic and the solution of the task was carried out on the basis of a wide range of materials from the practice of using the MFN principle and its interpretation, the theoretical sharpening of many aspects, and the use of methodological tools traditional for the humanities (law) sciences.THE RESEARCH RESULTS. During the development of the topic, the history of the formation and development of MFN principle, its significance for the international law order and the prospects for its use as a norm of international law, as a principle and method of regulation appear in a slightly new light.DISCUSSION AND CONCLUSIONS. Despite the extensive scientific literature on MFN principle, there are still many unresolved, contradictory opinions and positions about its nature and essence, its normative force and effectiveness, its impact on interstate relations and its place in the global legal system. MFN principle appears today not only as a norm and principle of international law, but also as a principle-institutio, as a method (mechanism) of regulation. At the same time, the scope of its application is expanding, and the regulatory method embedded in it allows for the use of MFN in other potentially suitable areas. MFN principle is turning into an unit of interbranch law formation. In the international trading system and the international trade law order, MFN principle until recently possessed cogent properties, merging into a kind of trinity with the principle of national treatment and the principle of non-discrimination. With the modern transformation of the international system and the world order, MFN principle, as a universal, global principle, is reproduced at the regional and interregional levels, undergoing fragmentation characteristic of international law as a whole. At the same time, MFN principle has become and remains an integral part of the internal content of many fundamental principles of international law, as well as part of the generalizing principle of peaceful coexistence of States and civilizations.